PERAN PROFITABILITAS DALAM MEMEDIASI MODAL KERJA DAN AKTIVITAS TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN REAL ESTATE - Fresiliasari, Oktavie; Widyakto, Adhi; Pradiptya, Adhi (ITB AAS Indonesia Surakarta, 2024)
Property and Real Estate is one of the service company sub-sectors listed as a public company in the Property, Real Estate and construction sectors on the Indonesia Stock Exchange (BEI). Property and real estate are still among the main choices for investors when investing funds. This is because shares of companies in the Property and Real Estate sector still offer potential for increases. The Property and Real Estate sector is one of the sectors that makes a fairly good contribution to economic growth in Indonesia. This research aims to describe and analyze the role of profitability in mediating working capital and activities on company value in real estate companies listed on the BEI in 2019-2022. This research variable uses independent variables, dependent variables and intervening variables. The object of this research is the financial reports of real estate companies listed on the IDX. The type of data used is quantitative data. The data source was obtained from secondary data through intermediaries or indirectly, namely data from real estate company financial reports for the 2018-2022 period. The data collection method uses library research. The analysis technique is descriptive analysis and smart PLS analysis. The data measurement method uses validity tests and reliability tests. Test the structural model using the coefficient of determination. Hypothesis testing uses structural equation modeling analysis with the smartPLS 3.0 program. Measurement model with devaluation reflection indicators with convergent and discriminant validity. The results of this research prove that Working capital (CR) has a significant positive effect on Profitability (ROA), activity (TATO) Has a positive effect on Profitability Policy (ROA), Working capital (CR) has no effect on company value (PBV), Working capital ( TATO) has a significant positive effect on company value (PBV), profitability (ROA) has a significant positive effect on company value (PBV), profitability (ROA) is able to mediate the effect of working capital (CR) on company value (PBV).